EVALUATION OF PHICOCYANIN PRODUCTION BY Anabaena variabilis USING DIFFERENT ORGANIC CARBON SOURCES - Warlley Rosa Cunha; Arthur Godoy Cottas; Thales Azevedo Teixeira; Juliana de Souza Ferreira (The Journal of Engineering and Exact Sciences)
Phycocyanin (PC) is one of the phycobiliproteins, pigments found in cyanobacteria, which can be used as natural dyes, antioxidants and fluorescent markers. This study aimed to investigate the effect of supplementation of the basal culture medium (BG110) of the cyanobacterium Anabaena variabilis with different sources of organic carbon in concentration of 1 g?L-1, evaluating the production of biomass and PC. The best condition obtained was the medium supplemented with glucose that produced 75.36 mg?g-1 PC, about 5 times greater than the control with 14.57 mg?g-1 PC. All supplemented media also showed higher biomass production compared to the basal medium, again to stand out for the glucose medium, presenting 0.29 g?L-1 of dry biomass.